2007
DOI: 10.1111/j.1540-9740.2007.05927.x
|View full text |Cite
|
Sign up to set email alerts
|

AIDS in Pregnancy, Part II: Treatment in the Era of Highly Active Antiretroviral Therapy and Management of Obstetric, Anesthetic, and Pediatric Issues

Abstract: International guidelines recommend resistance testing of maternal virus for all human immunodeficiency virus (HIV)-infected pregnant women. The use of highly active antiretroviral therapy leads to maximal virologic suppression, thus minimizing the risk of drug resistance, but it is available only in developed countries. In developing countries, the use of short-course regimens is becoming more widespread. Women infected with HIV may be at greater risk for complications during pregnancy, including ectopic pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Both decreased TG clearance and increased hepatic VLDL overproduction have been found in HIV-positive patients, and the hepatic increased lipogenesis correlates to IFN-α [20]. Again, by the level of immunological deficiency according to the CD4+ cell count, some authors [38,37,13] determined the level of plasma triglycerides, total cholesterol and HDL-C in HIV infected individuals and came to the same conclusion with an increase in immunological deficiency and clinical development of HIV infection, lipid profile disorders-indicated by an increase in triglycerides level and decrease concentrations of HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…Both decreased TG clearance and increased hepatic VLDL overproduction have been found in HIV-positive patients, and the hepatic increased lipogenesis correlates to IFN-α [20]. Again, by the level of immunological deficiency according to the CD4+ cell count, some authors [38,37,13] determined the level of plasma triglycerides, total cholesterol and HDL-C in HIV infected individuals and came to the same conclusion with an increase in immunological deficiency and clinical development of HIV infection, lipid profile disorders-indicated by an increase in triglycerides level and decrease concentrations of HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…Since then several studies have been undertaken to examine other regimens that would be less complex and more easily executed in developing countries, however none have shown such extensive efficacy as the use of AZT-containing HAART. Although there have been no randomised controlled clinical trials containing a placebo group with HAART in pregnancy, several retro/prospective cohort studies have shown that MTCT rates are lower with HAART than with than AZT alone [30]. Cooper et al showed decreased rates of MTCT with increasing number of ARVs administered: 20% with no treatment, 10.4% with AZT monotherapy, 3.8% with dual therapy and 1.2% with HAART [31].…”
Section: Haart During Pregnancymentioning
confidence: 99%